2001
DOI: 10.1007/pl00011364
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localisation of Hypericin in Human Glioblastoma and Carcinoma Cell Lines

Abstract: Hypericin, a natural polycyclic quinone extracted from Hypericum perforatum, has been recently shown to be a powerful sensitiser for photodynamic therapy (PDT). However, its intracellular localisation remains unclear and contradictory. In the present work we compared the intracellular localisation of hypericin in three cultured cell lines (adenocarcinoma cells WiDr, carcinoma cells NHIK 3025 and glioblastoma cells D54Mg) with the distribution of fluorescent probes specific to lysosomes (LysoTracker Blue DND-22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 27 publications
6
48
1
Order By: Relevance
“…Illumination of HYtreated glioblastoma cells (2 h/2.5 μM) at 595 nm with light doses as low as 0.15-0.20 J/cm 2 resulted in a decrease in cell survival to 50% (ID 50 -values); after exposure to 0.4 J/cm 2 cell survival was reduced to about 10% as compared to nonilluminated controls. These results are basically in line with results obtained for other cell lines (11,13,16). In the case of AY-27 cells (transitional cell carcinoma), incubated with HY (0.05-10 μM/2 h) and illuminated (595 nm) of under quite similar experimental conditions as used in the present study, an incubation concentration of about 2.5 μM was required to reduced cell survival to 50% (IC 50 -value) when cells were illuminated with 0.45 J/cm 2 (12).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Illumination of HYtreated glioblastoma cells (2 h/2.5 μM) at 595 nm with light doses as low as 0.15-0.20 J/cm 2 resulted in a decrease in cell survival to 50% (ID 50 -values); after exposure to 0.4 J/cm 2 cell survival was reduced to about 10% as compared to nonilluminated controls. These results are basically in line with results obtained for other cell lines (11,13,16). In the case of AY-27 cells (transitional cell carcinoma), incubated with HY (0.05-10 μM/2 h) and illuminated (595 nm) of under quite similar experimental conditions as used in the present study, an incubation concentration of about 2.5 μM was required to reduced cell survival to 50% (IC 50 -value) when cells were illuminated with 0.45 J/cm 2 (12).…”
Section: Discussionsupporting
confidence: 82%
“…by receptor-mediated endocytosis or pinocytosis, rather than by (passive) diffusion. In contrast, no noticeable difference in the HY staining pattern in WiDr cells (human colon carcinoma cell line) was found when comparing fluorescence images after 1 h incubation at 4˚C or at room temperature by Uzdensky et al (16). Consequently, they concluded that HY penetrates cells mostly by diffusion.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…, Saczko et al 2007), Golgi apparatus (Rodal et al 1998, Fabris et al 2001, endoplasmic reticulum (Rodal et al 1998, Uzdensky et al 2001, endosomes and lysosomes (Roberts & Berns 1989, Berg et al 1990b) and the microtubuli (Berg et al 1990a). Clinically relevant PSs for cancer treatment do usually not localize to the nucleus because of their negative charge (Evensen & Moan 1982).…”
mentioning
confidence: 99%